Аналоги радянських протоколів допитів у системі документообігу ОУН(б) і УПА (1940-і рр.) - Ковальчук, В. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2007)
The author made source study analysis of interrogation transcript of OUN(b) security service as well as UPA field police.